Enhanced resistance of Panaeus monodon against Vibro harveyi infection using alibutbut (Tabernaemontana pandacaqui Poi) fortified feeds. - Marmol, Roda Ann Y.
Alibutbut (Tabernaemontana pandacaqui Poir.) powder , 250 mg, was incorporated to a kilo commercial shrimp feed in order to enhance resistance of postlarvae Penaeus monodon shrimps. Healthy post larvae fry was fed with different treatment for seven (7) days. Treatments include negative control (plain commercial feed). Trials with three replicates were conducted., The efficacy of Alibutbut-based commercial feed was supported by the fact that the mortality in the positive control ws 23.33 percent while post larvae Penaeus monodon fed with alibutbut-based fortified feeds show low mortality of 10-20 percent and 43.33 percent mortality in the negative control, after immersion to 10 raise to the 6th power CFU/ml Vibrio harveyi for 48 hours. The fortified diet was effective in developing resistance of P. monodon (PL20) against Vibrio harveyi infection. However, there is a significant difference in the level of infection on shrimps that survived between the positive control, where the colony count is 3.0 x 10 raise to the 5th power CFU/ml and 1.67 x 10 raise to the 5th power CFU/ml for alibutbut-based fortified feeds. Chloramphenicol used in the positive control has developed the resistance of the Vibrio harveyi pathogen causing the lowering of its antivibriotic activity. Presence of fractions of alkaloids, saponins and terpenes in alibutbut are possible sources of metabolites, which exhibits antivibriotic property. The incorporation of ethnobotanicals like alibutbut in the feed formulation likewise proved effectie and feasible. Therefore, the use of alibutbut-based fortified feed can be an alternative for the use of antibioticslike Chloramphenicol.